2017
DOI: 10.9734/bjmmr/2017/33535
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Dynamic Thiol-Disulfide Homeostasis in Alopecia Areata Patients

Abstract: Background: Thiols are antioxidant, organic compounds containing sulfhydryl group on their active sites. They have important roles on preventing oxidative stress. The thiol disulfide homeostasis has a vital importance in organism. Thiol disulfide imbalance is an early indicator of oxidative stress. Alopecia areata is an autoimmune skin disorder characterized with scar-free hair loss. Its pathogenesis is still unclear. Thiol disulfide homeostasis in these patients has not been studied at all. Objective: To eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Knowing the function of thiols involved in the antioxidant system is therefore becoming increasingly important in terms of understanding several diseases associated with oxidative stress, including COPD [19]. Studies investigating the relation between oxidative stress and TDH have shown that such homeostasis is impaired in oxidative terms in patients with acute myocardial infarction, migraine, alopecia or chronic urticaria, in pregnant women with hyperemesis gravidarum (compared to normal gravidas), and in workers exposed to polycyclic aromatic hydrocarbons [14][15][16][33][34][35]. Babaoglu et al [36] assumed the presence of oxidative stress in COPD and investigated TDH in other subgroup diseases causing lower airway obstruction, such as asthma and asthma-COPD overlap syndrome (ACOS).…”
Section: Discussionmentioning
confidence: 99%
“…Knowing the function of thiols involved in the antioxidant system is therefore becoming increasingly important in terms of understanding several diseases associated with oxidative stress, including COPD [19]. Studies investigating the relation between oxidative stress and TDH have shown that such homeostasis is impaired in oxidative terms in patients with acute myocardial infarction, migraine, alopecia or chronic urticaria, in pregnant women with hyperemesis gravidarum (compared to normal gravidas), and in workers exposed to polycyclic aromatic hydrocarbons [14][15][16][33][34][35]. Babaoglu et al [36] assumed the presence of oxidative stress in COPD and investigated TDH in other subgroup diseases causing lower airway obstruction, such as asthma and asthma-COPD overlap syndrome (ACOS).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that TDH was no changed in patients with alopecia areata, an autoimmune disease characterized scar-free hair loss. This may result from patients which has mild alopecia areata disease [75].…”
Section: Dermatologic Disordersmentioning
confidence: 99%
“…Kilinc et al (21) reported that the disulfide/native thiol and native thiol/total thiol ratios and native thiol, total thiol, and disulfide values were similar in AA patients and the control group. Akbas et al (8) reported that disulphide/thiol ratio increased in chronic urticaria and increased oxidative stress reduced disulphide ratio in chronic stage.…”
Section: Discussionmentioning
confidence: 97%
“…Kilinc et al (21) reported that thiol/disulfide values were not associated with gender, disease duration, number of lesions, or recurrence frequency in AA patients. Akar et al (18) reported that oxidation was augmented in the acute stage compared to the chronic stage.…”
Section: Discussionmentioning
confidence: 99%